2020
DOI: 10.9734/ijecc/2020/v10i130171
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Top Soil Properties under Forested and Deforested Zones: Implications for the Environment

Abstract: An investigation was carried out to examine the properties of top soils between 0 and 15cm under both deforested and forested zones in Bowen University, Iwo, Nigeria. Top soil samples in the deforested zone was taken from the Main Gate area of the institution while that of the forested zone was taken from the forested area opposite staff quarters of the University. The soil samples were subjected to standard laboratory tests in the University central laboratory. The results showed that deforested soil has sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Garbuio et al (2012) further revealed that the effects of human activities vary with land use, ranging from agricultural wastes such as farm animal sewerage and fertilizer runoff to industrial and commercial wastes of every conceivable type and magnitude. In the same vein, Biyogue (2016) and Odekunle et al (2020) in their separate investigations revealed that deforestation has implied effects on the soils when compared with the soil under forest. Both studies found that the bulk density, cationexchange capacity (CEC), soil organic carbon, total nitrogen, and phosphorous values were higher in soils under forests than that under deforestation.…”
Section: Open Access Edited Bymentioning
confidence: 87%
“…Garbuio et al (2012) further revealed that the effects of human activities vary with land use, ranging from agricultural wastes such as farm animal sewerage and fertilizer runoff to industrial and commercial wastes of every conceivable type and magnitude. In the same vein, Biyogue (2016) and Odekunle et al (2020) in their separate investigations revealed that deforestation has implied effects on the soils when compared with the soil under forest. Both studies found that the bulk density, cationexchange capacity (CEC), soil organic carbon, total nitrogen, and phosphorous values were higher in soils under forests than that under deforestation.…”
Section: Open Access Edited Bymentioning
confidence: 87%